Effectiveness of Waste Shrimp Shell as Chitosan Polymer Medium (CPM) Mask In Reducing Cigarette Smoke (Future Science, 2022)
Shrimp shell waste contains chitin which is considered potential as a mask coating material to remove toxic substances in cigarette smoke. The masks were made using Chitosan Polymer Medium (CPM) with the spray coating method. Therefore, this study aims to determine the optimal concentration of reducing nicotine, constant, and reduced capacity of Chitosan Polymer Medium (CPM). The variations used were the type of CPM, the total spraying was 3 sprays, 5 sprays, and 7 sprays, and the concentration of CPM was 10,000 ppm, 20,000 ppm, 30,000 ppm, 40,000 ppm, and 50,000 ppm. The best result is the nicotine removal percentage is 99.98%, and the adsorption capacity is 7,0376 mg/g. The results showed that shrimp shell CPM was effective as an adsorbent in the adsorption process to remove nicotine in cigarette smoke.